Compliance and Quality Control Monitoring of Diagnostic X ray Facilities in Dar es Salaam City, Tanzania (Brazilian Journal of Radiation Sciences, 2017)
The compliance evaluation and quality control measurements on 14 diagnostic X ray units were carried out. The results on legal compliance show that 43 % of X ray facilities operated without or with an expired license. The rest of the centers were new and had already applied for license and others had valid licenses. For basic requirements, the results shows that 57 % of X ray facilities did not have the changing cubicles, 36 % of X ray facilities did not post radiation warning sign and symbols also 64 % of units were found either without protective gear or operated by unqualified personnel. The QC test results showed that 93 % had X-ray tube voltage within the tolerance limit of 10 % and HVL ≥ 2.3 mmAl, at 80 kV was observed in all 14 units whereas 100 % of exposure had acceptable kV reproducibility within the tolerance limit of 5 %. Of the X-ray generators assessed, 86 % had tolerable mAs linearity. 79 % and 93 % had acceptable beam alignment and light beam diaphragm. Of the assessed units, 57 % had tube leakage < 1000 µGy/hr at 1 m for true 80 kV. For shielding tests, 50 % of units had radiation levels above 0.5 µSv/hr at the main door leading to the X ray rooms and the registration area. The dose rates > 10 µSv/hr were recorded at viewing windows, walls and doors of control cubicles and behind the doors of changing cubicles. These dose rates indicating higher health risk to workers and member of public.